(untitled) (Cardiovascular Journal, 2012)
Myxomas are rare tumours but are the most common benign tumours of the heart. They can arise from any heart chamber. However, they arise more frequently from the left atrium. They have rarely been described as originating in early age. A case of left atrial myxoma successfully removed using cardiopulmonary bypass in a 8-year-old child is presented. Review of the literature emphasizes the rarity and clinically aggressive behavior of this tumor in this age group. The object of this case report is to present myxoma in children and to evaluate possible differences between young and adult patients. DOI: http://dx.doi.org/10.3329/cardio.v4i2.10462 Cardiovasc. j. 2012; 4(2): 171-173